Analysis of User Proficiency and Involvement in a Citizen Science Project - Luciano Vieira Dutra, Marinalva Dias Soares; Santos, Rafael; Vijaykumar, Nandamudi L.; Dutra, Luciano Vieira (Cadernos do IME - Série Informática, 2010)
Due to its popularity, ubiquity and relatively low cost of access, the Internet has become a major channel for interaction between people in different forms and for different purposes. One relatively new interaction paradigm is exemplified by citizen science, which allows scientists and common people to collaborate in different ways to solve a particular scientific problem. Several citizen science projects are already in execution, some of those being very successful both for the scientific purpose and in the sense of engaging the participants, showing its potential for science and education. In this paper is presented a citizen science project to voluntarily label imprecisely segmented images and show whether patterns and trends among the users can be identified through their proficiency and involvement with the project. Keywords: Citizen science, collective intelligence, userbehavior, image segmentation, image labeling.